2005
DOI: 10.1038/sj.jhh.1001861
|View full text |Cite
|
Sign up to set email alerts
|

Association between arterial stiffness and platelet activation

Abstract: Increased arterial stiffness is strongly associated with atherosclerosis, while platelet activation is an important trigger of thrombotic events in patients with atherosclerosis. However, little is known about the effect of arterial stiffness on platelet activation. We therefore investigated the association between arterial stiffness and platelet activation in 38 normal volunteers (20 men and 18 women) aged 23-77 years (mean ¼ 49715 years). Arterial stiffness was assessed by measuring brachialankle pulse wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
(62 reference statements)
3
14
0
3
Order By: Relevance
“…Release of growth factors by activated platelets may lead to vascular changes 20 . Yamasaki et al showed that platelet activation was related to increased arterial stiffness 21 . In our study, platelet count was significant determinant of stiffness index.…”
Section: Discussionsupporting
confidence: 60%
“…Release of growth factors by activated platelets may lead to vascular changes 20 . Yamasaki et al showed that platelet activation was related to increased arterial stiffness 21 . In our study, platelet count was significant determinant of stiffness index.…”
Section: Discussionsupporting
confidence: 60%
“…The present findings agree with those from at least three cross-sectional studies of individuals at low to moderate CVD risk, in which associations were found between several markers of in vivo platelet activation and both cfPWV(5) and baPWV(4,7). Though the present observational study cannot establish that arterial stiffening causes increased platelet activation, there are several potential mechanisms that may explain this prospective association.…”
Section: Discussionsupporting
confidence: 92%
“…Previous small cross-sectional studies of apparently healthy adults observed associations between increased platelet activation and increased carotid-femoral pulse wave velocity (cfPWV) (4,5), a measure of aortic stiffness and independent predictor of cardiovascular events (6). Other studies of apparently healthy adults have found associations between several markers of in vivo platelet activation and brachial-ankle pulse wave velocity (baPWV), a measure of mixed central (aortic) and peripheral arterial stiffness (4,7). Such cross-sectional associations may be explained by either the influence of activated platelets on the vasculature or the effect of vascular damage and dysfunction on circulating platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is an essential process in the development of major cardiovascular and cerebrovascular events (Yamasaki et al 2005). Atherosclerosis is one of the most important factors for the development of hypertension and leads to target organ damage and cardiovascular events (Thuillez and Richard 2005).…”
Section: Introductionmentioning
confidence: 99%